2021
DOI: 10.15403/jgld-3992
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, Real-life, Observational Study in Treating Outpatient Ulcerative Colitis with Golimumab

Abstract: Background and Aims: Several studies have found Golimumab (GOL) effective and safe in the short-term treatment of ulcerative colitis (UC), but few long-term data are currently available from real world. Our aim was to assess the long-term real-life efficacy and safety of GOL in managing UC outpatients in Italy. Methods: A retrospective multicenter study assessing consecutive UC outpatients treated with GOL for at least 3-month of follow-up was made. Primary endpoints were the induction and maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Anti-TNF therapies approved for the treatment of both CD and UC, include infliximab and adalimumab. Golimumab has also been evaluated for use in UC [ 26 ]. Unfortunately, one-third of patients are primary non-responders, and dose intensification is needed in 23 to 46% of responders, with drug discontinuation occurring in 5% to 12% of patients per year [ 27 ].…”
Section: Therapeutic Management Of Chronic Intestinal Disordersmentioning
confidence: 99%
“…Anti-TNF therapies approved for the treatment of both CD and UC, include infliximab and adalimumab. Golimumab has also been evaluated for use in UC [ 26 ]. Unfortunately, one-third of patients are primary non-responders, and dose intensification is needed in 23 to 46% of responders, with drug discontinuation occurring in 5% to 12% of patients per year [ 27 ].…”
Section: Therapeutic Management Of Chronic Intestinal Disordersmentioning
confidence: 99%
“…GLM is a subcutaneously administered fully human anti-tumor necrosis factor-α (TNF-α) antibody. Several clinical trials [2,3] and real-world data [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] outside Japan have demonstrated the clinical efficacy and safety of GLM in induction and maintenance therapy in patients with moderate-to-severe active UC. In addition, the PURSUIT-J study showed that GLM treatment for 54 weeks maintained clinical efficacy and safety through week 54 among induction responders in biologic-naïve Japanese patients with moderate-to-severe active UC [22].…”
Section: Introductionmentioning
confidence: 99%